The Role of Coretax Implementation, Tax Knowladge, and Tax Sanctions In Encouraging Individual Taxpayer Compliance In Malang City - Satria, Muhamad Ilham; Cahyaningtyas, Fadila cahyaningtyas (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The primary objective of this study is to meticulously analyze the role of coretax implementation, tax knowladge, and tax sanctions in encouraging individual taxpayer compliance in Malang City. The central focus is specifically directed toward assessing the effectiveness of tax administration modernization in elevating the level of taxpayer compliance. Background Problems: Although the government has developed the Core Tax Administration System (Coretax), the degree of taxpayer compliance remains comparatively low.. Many taxpayers have not yet understood tax procedures, and some others have not fulfilled their obligations correctly, thus the modernization of the system has not fully influenced compliance behavior. Novelty: The novelty of this research lies in its analytical focus on the effectiveness of Coretax implementation on Personal Taxpayer compliance in Malang City, a context that has rarely been studied in depth. Furthermore, this research integrates the variables of tax knowledge and tax sanctions to examine how these two factors play a role in strengthening or weakening the impact of tax administration modernization. Studies concerning Coretax within the Personal Taxpayer segment are still relatively limited, thus this research provides a new empirical contribution regarding the factors influencing compliance in the era of digitalization of tax services. Research Methods: This study employs a quantitative research design and collected data using a purposive sampling technique form 77 personal taxpayer respondents. The statistical analysis, performed with SPSS software, included several steps validity and reliability testing, classical assumtion tests, and hypothesis testing via multiple linear regression analysis, t-test, and calculating the coefficient of determination (R2). Finding/Results: The research findings indicate that the implementation of coretax does not have a significant effect on taxpayer compliance. In contrast, tax knowladge and tax sanctions are proven to have a positive and significant impact on improving taxpayer compliance. Tax knowledge is the factor with the greatest impact, while sanctions remain an important instrument in improving compliance through deterrent effects and law enforcement. Conclusion: The research concludes that the increase in taxpayer compliance is more influenced by the taxpayer's comprehension of tax regulations and their perception of sanctions, compared to the modernization of the administrative system through Coretax. This finding implies the necessity of increasing tax literacy, optimizing Coretax socialization, and ensuring consistency in the application of sanctions as strategic steps to strengthen tax compliance